Ancient Chinese Marriage Culture: Budaya Perkawinan Masyarakat Tiongkok Kuno - Yusuf Arifin, Yohan (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Chinese culture is one of the oldest cultures in the world. Every existing cultural heritage has its own characteristics and uniqueness. This cultural heritage develops from time to time so it is worth studying to open our insights into related cultures. This study aims to discuss one of the cultural heritages of China, namely the culture of marriage that occurred in ancient Chinese society. This research is a qualitative descriptive study using literature related to the topics to be discussed in this study as reference material. It is hoped that through this research, it can provide benefits to those who study Chinese culture, especially the marriage culture of ancient Chinese society.